Merit Order as a Generation Portfolio Optimization Mechanism in PLN and PLN Nusantara Power: A Systematic Analysis of Operational Efficiency, PJBTL Contract Structure, and Digital Transformation (International Journal of Economics and Management Research, 2026)
This study aims to analyze the role of the merit order as a portfolio optimization mechanism for power generation within PLN and PLN Nusantara Power (PLN NP) by linking three key dimensions: operational efficiency, the structure of Power Purchase Agreements (PJBTL), and digital transformation. The method employed is a Systematic Literature Review (SLR) of journal articles, corporate reports, regulations, and official documents related to merit order, PJBTL, generation portfolio strategy, and the digitalization of Indonesia’s electricity system over the period 2010–2025. The findings indicate that the implementation of the merit order in PLN and PLN NP has evolved from a classical model based solely on marginal cost into a “hybrid merit order” that integrates thermal efficiency indicators (SFC, NPHR), unit reliability (EAF, EFOR), and generation mix, supported by digital platforms such as Dispatch Optimization, i-CORE, and the Nusantara InnoVision Center. The PJBTL structure is found to be ambivalent: IPP contracts based on take-or-pay schemes and long-term primary energy contracts limit dispatch flexibility and reduce the effectiveness of the merit order, while PJBTL arrangements with industrial customers contribute to stabilizing base load and expanding operational flexibility. From a commercial perspective, this study confirms that growth in electricity sales only improves performance when additional demand is supplied by low-cost units that are competitive within the merit order. Otherwise, increased TWh sales risk becoming “pseudo-growth,” where production costs (BPP) remain high and margins do not significantly improve.